2009
DOI: 10.1007/s00122-009-1006-5
|View full text |Cite
|
Sign up to set email alerts
|

Saturation and comparative mapping of the genomic region harboring Hessian fly resistance gene H26 in wheat

Abstract: Resistance gene H26, derived from Aegilops tauschii Coss., is one of the most eVective R genes against the Hessian Xy [Mayetiola destructor (Say)], an important pest of wheat (Triticum aestivum L.). Using a limited number of PCR-based molecular markers a previous study mapped H26 to the wheat chromosomal deletion bin 3DL3-0.81-1.00. The objectives of this study were to saturate the chromosomal region harboring H26 with newly developed PCR-based markers and to investigate the collinearity of this wheat chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…In this study, we used a RIL population instead of F 2 as reported in most previous studies (Dweikat et al 2002;Martín-Sánchez et al 2003;Kong et al 2005Kong et al , 2008Liu et al 2005bLiu et al , 2005cYu et al 2009) to improve phenotyping accuracy. RILs have a high recombination frequency resulting from multiple meiotic events that occurred during repeated selfing (Jansen 2003), and a high level of homozygosity that enables replicated phenotyping across different environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used a RIL population instead of F 2 as reported in most previous studies (Dweikat et al 2002;Martín-Sánchez et al 2003;Kong et al 2005Kong et al , 2008Liu et al 2005bLiu et al , 2005cYu et al 2009) to improve phenotyping accuracy. RILs have a high recombination frequency resulting from multiple meiotic events that occurred during repeated selfing (Jansen 2003), and a high level of homozygosity that enables replicated phenotyping across different environments.…”
Section: Discussionmentioning
confidence: 99%
“…All HFR genes from the D genome were derived from Ae. tauschii, the D genome donor of common wheat (Martin et al 1982;Gill et al 1986Gill et al , 1991aRaupp et al 1993;Cox and Hatchett 1994;Ratcliffe and Hatchett 1997;Sardesai et al 2005), and located on chromosomes 1D, 3D, 4D, and 6D (Gill et al 1987;Raupp et al 1993;Cox and Hatchett 1994;Martín-Sánchez et al 2003;Liu et al 2005;Sardesai et al 2005;Wang et al 2006;Zhao et al 2006;Yu et al 2009;Yu et al 2010). In addition to these HFR genes identified from wheat, H21 and H25 were derived from rye (Secale cereale) and transferred to common wheat (Friebe et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the polymorphic STS markers were identified, they were analyzed on the four BC 2 F 1 plants (0406, 0439, 0696 and 0735) and their derived 36 BC 2 F 3 individuals, along with Rusty, DAS15, and three CS nulli-tetrasomic lines N2AT2D, N2BT2A, and N2DT2A. The polymerase chain reaction (PCR) amplification was carried out as described by Yu et al (2009). The PCR products were electrophoresed on 6 % polyacrylamide gels and stained with Gel-Red, then scanned with a Typhoon 9410 imager (GE Healthcare, Waukesha, WI, USA).…”
Section: Sequence-tagged Site (Sts) Marker Development and Validationmentioning
confidence: 99%
“…The H gene that is chosen for the region is the one for which there is the least virulence within populations. Only a few H genes provide this all-inclusive resistance, for example, the H26 gene discovered in an ancestor of wheat, Aegilops tauschii (Cosson) (Cox et al 1994, Yu et al 2009). Stacking R genes also is expected to provide durable resistance but it requires reliable molecular markers, such as those for H9, H13, H18, H26, and H32 (Dweikat et al 1997;Liu et al 2005;Wang et al 2006;Yu et al 2009Yu et al , 2010.…”
mentioning
confidence: 99%